2021
DOI: 10.1126/science.abe7291
|View full text |Cite
|
Sign up to set email alerts
|

Extreme altitudes during diurnal flights in a nocturnal songbird migrant

Abstract: Billions of nocturnally migrating songbirds fly across oceans and deserts on their annual journeys. Using multisensor data loggers, we show that great reed warblers (Acrocephalus arundinaceus) regularly prolong their otherwise strictly nocturnal flights into daytime when crossing the Mediterranean Sea and the Sahara Desert. Unexpectedly, when prolonging their flights, they climbed steeply at dawn, from a mean of 2394 meters above sea level to reach extreme cruising altitudes (mean 5367 and maximum 6267 meters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…The tracked nightjars reached altitudes just below 5000 masl, which is similar to recordings of another trans-Saharan migrant, the Eurasian hoopoe, Upupa epops , but considerably lower than the maximum flight altitudes above 6000 masl of great reed warblers, Acrocephalus arundiaceus ( Liechti et al, 2018 ; Sjöberg et al, 2021 ), and great snipes, Gallinago media (above 8000 masl; Lindström et al, 2021 ). The nightjars flew at the highest altitudes during the spring crossing of the Sahara desert, which conforms well with the general pattern of altitude distribution of avian migrants based on radar observations in Europe and west-Saharan Africa (reviewed in Bruderer et al, 2018 ).…”
Section: Discussionsupporting
confidence: 68%
“…The tracked nightjars reached altitudes just below 5000 masl, which is similar to recordings of another trans-Saharan migrant, the Eurasian hoopoe, Upupa epops , but considerably lower than the maximum flight altitudes above 6000 masl of great reed warblers, Acrocephalus arundiaceus ( Liechti et al, 2018 ; Sjöberg et al, 2021 ), and great snipes, Gallinago media (above 8000 masl; Lindström et al, 2021 ). The nightjars flew at the highest altitudes during the spring crossing of the Sahara desert, which conforms well with the general pattern of altitude distribution of avian migrants based on radar observations in Europe and west-Saharan Africa (reviewed in Bruderer et al, 2018 ).…”
Section: Discussionsupporting
confidence: 68%
“…It should be stressed that, despite the strong preference for staying low, birds in this and many other studies [ 3 , 8 , 10 , 14 , 17 , 25 , 52 ] occasionally climb to great altitudes. Indeed, our conditional logistic mixed effect modelling evaluating the contribution of the conditions aloft and flight altitude explained 67% and 61% of the variation in far eastern curlew and whimbrel respectively.…”
Section: Discussionmentioning
confidence: 49%
“…However, empirical studies based on radar observations have found mixed support for this hypothesis [ 6 , 19 , 20 ]. Tracking of great reed warblers and black-tailed godwits showed that their high altitude flights were associated with high air temperature at low altitude, suggesting they were potentially avoiding overheating [ 14 , 25 ] and conserving their water balance. Our finding showed that altitude at which both far eastern curlew and whimbrel chose to fly were neither directly related to air temperature nor relative humidity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations